Total factor productivity growth in Costa Rica and macroeconomic instability - Robles, Edgar A (2021)
This paper uses the growth accounting methodology, called Two- Deflator Approach, to estimate Total Factor Productivity (TFP) in Costa Rica between 1960 and 2019. The results indicate that 14% of economic growth is explained by the growth of TFP. The rest of economic growth is associated with contributions of capital (52%) and labor (34%), which have been positive during all decades of this period. Regarding the contribution of labor, its contribution to economic growth has been due to the quantity and not the quality of the workforce, except for the first (1960-1969) and last (2010-2019) periods, where quality contributed positively to economic growth. In terms of changes, the results show that 69% of the change in the growth rate during the period is explained by changes in TFP; the remaining 31% is explained by changes in the contributions of the factors of production (labor and capital). Once the TFP is calculated, a GARCH model is used to estimate the relationship between the macroeconomic instability and TFP growth. Thus, evidence was found that TFP growth in Costa Rica is negatively affected by high inflation. Moreover, TFP growth benefits from higher openness to international trade, measured by the sum of imports and exports to GDP, and TFP is harmed when there is greater volatility of financial deepening, measured by the ratio from M1 or M2 to GDP.